Pricing Strategies Application Amongst the Top E-commerce Southeast Asian Countries - Masyhuri, Muhammad (Asian Journal of Management Analytics, 2023)
The Internet economy plays an important role in the development of the country's economy. In fact, more than 60% of customers worldwide cite price as the first reason for visiting an e-commerce website. The purpose of this study is to discuss the pricing strategy of the four current leading e-commerce marketplaces in Southeast Asian countries (SEA). The methodology used for this research was descriptive analysis, adapting and modifying the work of Rekettye & Liu (2018) and Skripak et al. (2018). It was found that the top four e-commerce companies use a strategy of market penetration and flexible pricing to compete and maintain their business in the market region.